During high salt treatment myeloid p38α/MAPK fosters osteoclast activity and inflammatory macrophage responses promoting orthodontic tooth movement - Schröder, Agnes; Fischer, Florian; Reinert, Beatrice; Jantsch, Jonathan; Proff, Peter; Paddenberg-Schubert, Eva; Kirschneck, Christian (Frontiers in Immunology, 2025)
IntroductionDuring orthodontic tooth movement, sterile inflammatory processes and alveolar bone resorption occur in the periodontal ligament, involving myeloid cells such as macrophages and osteoclasts. The myeloid p38α/MAPK (mitogen-activated protein kinase) not only regulates the inflammatory response of macrophages and osteoclast differentiation but also the activation of the osmoprotective transcription factor NFAT5 (nuclear factor of activated T cells 5) under high-salt conditions. Therefore, this study aims to investigate the relative role of myeloid p38α/MAPK in orthodontic tooth movement as a function of extracellular salt content.Material and methodsMacrophages and osteoclasts were differentiated from the bone marrow of mice lacking p38α/MAPK expression in myeloid cells (p38αΔmyel) and controls for RNA analysis and calcium phosphate resorption assay. Controls and p38αΔmyel mice were fed a low or a high salt diet for a total of two weeks. One week after the start of the diet, an elastic band was inserted between the first and second molar to induce orthodontic tooth movement. Atomic absorption spectrometry was used to assess the sodium balance of the jaw bone tissue. RNA was isolated from the periodontium of the first molar, osteoclast numbers and extent of orthodontic tooth movement were assessed. ResultsNfat5 mRNA was increased in macrophages and osteoclasts in vitro and in the periodontium in vivo after high salt treatment in control mice but not in p38αΔmyel mice. While there was no salt effect on interleukin-6 (Il6) gene expression, prostaglandin endoperoxide synthase-2 (Ptgs2) mRNA was upregulated in control but not in p38αΔmyel mice in vitro and in vivo. p38α/MAPK deletion increased osteoclast numbers after low and high salt diet. Of note, deletion of p38α/MAPK elevated osteoclast activity under control salt conditions but reduced osteoclast activity under high salt conditions. High-salt diet resulted in increased sodium ion deposition in the jaw of both genotypes, while tooth movement was only increased in control mice. In p38αΔmyel mice, high salt diet reduced the extent of orthodontic tooth movement, which could be explained by the reduced bone resorption of osteoclasts.ConclusionWe conclude that myeloid p38α/MAPK promotes macrophage Ptgs2 expression and osteoclast activity in response to extracellular salt levels, thereby supporting orthodontic tooth movement.